Potential Cooperation, Uneven Capacity: Reassessing South–South Cooperation between Indonesia and Timor-Leste in Renewable Energy Development - Silvia Dian Anggraeni; Iqbal Ramadhan; Rusdi J. Abbas (Institute of International Studies, 2026)
This study critically examines the potential for South-South Cooperation (SSC) between Indonesia and Timor-Leste in the development of renewable energy in the border region. Although SSC is normatively described as a form of horizontal, solidarity-based cooperation among developing countries, this article argues that disparities in institutional capacity and developmental positions can hinder the realization of truly mutually beneficial partnerships within the Global South. Drawing on the key modes and principles of SSC—including horizontality, demand-driven cooperation, mutual benefits, cultural affinity, and knowledge transfer—this study analyzes how renewable energy cooperation is envisioned and structured from Indonesia’s perspective. Using a qualitative approach, this research relies on in-depth interviews with government agencies, think tanks, and local non-governmental organizations (NGOs), supplemented by policy documents and secondary literature. Findings indicate that border regions hold significant potential for renewable energy cooperation, particularly in the development of wind and hydro power. However, a centralized governance structure, uneven institutional capacity, and limited political commitment hinder the emergence of fully horizontal cooperation. This article argues that while SSC offers an alternative framework to North-South development relations, the potential cooperation between Indonesia and Timor-Leste also reveals the possibility of asymmetrical relations within the Global South itself. This study contributes to critical debates on SSC, postcolonial development, and energy transition in border regions.